(untitled) (Journal of Hama University, 2019)
The study aims to show the impact of quality of service on the relationship between market orientation and financial performance. A field study is on Syrian banks in the city of Aleppo. In order to achieve the objective of the research, a questionnaire is designed and distributed to branch managers, their deputies and employees in the administrative departments, where the number of questionnaires distributed are(85), but the valid for analysis has reached (50) questionnaires. The study concludes that: - Market orientation has a direct impact on financial performance. - Quality of service has an impact on financial performance. - The quality of service interaction with market orientation will increase financial performance